Plumbagin Regulates Snail to Inhibit Hepatocellular Carcinoma Epithelial-Mesenchymal Transition in vivo and in vitro - Du YQ; Yuan B; Ye YX; Zhou FL; Liu H; Huang JJ; Wei YF (Journal of Hepatocellular Carcinoma, 2024)
Yuan-Qin Du,1,* Bin Yuan,1,* Yi-Xian Ye,1 Feng-ling Zhou,1 Hong Liu,1 Jing-Jing Huang,2 Yan-Fei Wei3,4 1Graduate School, Guangxi University of Traditional Chinese Medicine, Nanning, 530200, People’s Republic of China; 2The First Affiliated Hospital of Guangxi University of Chinese Medicine, Nanning, 530024, People’s Republic of China; 3Department of Physiology, Guangxi University of Traditional Chinese Medicine, Nanning, 530200, People’s Republic of China; 4Guangxi Key Laboratory of Translational Medicine for Treating High-Incidence Infectious Diseases with Integrative Medicine, Nanning, 530200, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan-Fei Wei, Department of Physiology, Guangxi University of Traditional Chinese Medicine, No. 13 Wu He Road, Nanning, 530200, People’s Republic of China, Tel/Fax +86-771-4733794, Email weiyanfei@gxtcmu.edu.cnBackground/Aims: Plumbagin (PL) has been shown to effe ctively inhibit autophagy, suppressing invasion and migration of hepatocellular carcinoma (HCC) cells. However, the specific mechanism remains unclear. This study aimed to investigate the effect of PL on tumor growth factor (TGF)-β-induced epithelial-mesenchymal transition (EMT) in HCC.Methods: Huh-7 cells were cultured, and in vivo models of EMT and HCC-associated lung metastasis were developed through tail vein and in situ injections of tumor cells. In vivo imaging and hematoxylin and eosin staining were used to evaluate HCC modeling and lung metastasis. After PL intervention, the expression levels of Snail, vimentin, E-cadherin, and N-cadherin in the liver were evaluated through immunohistochemistry and Western blot. An in vitro TGF-β-induced cell EMT model was used to detect Snail, vimentin, E-cadherin, and N-cadherin mRNA levels through a polymerase chain reaction. Their protein levels were detected by immunofluorescence staining and Western blot.Results: In vivo experiments demonstrated that PL significantly reduced the expression of Snail, vimentin, and N-cadherin, while increasing the expression of E-cadherin at the protein levels, effectively inhibiting HCC and lung metastasis. In vitro experiments confirmed that PL up-regulated epithelial cell markers, down-regulated mesenchymal cell markers, and inhibited EMT levels in HCC cells.Conclusion: PL inhibits Snail expression, up-regulates E-cadherin expression, and down-regulates N-cadherin and vimentin expression, preventing EMT in HCC cells and reducing lung metastasis.Keywords: plumbagin, hepatocellular carcinoma, epithelial-mesenchymal transition, pulmonary metastasis, Snail